2018
DOI: 10.1029/2017pa003310
|View full text |Cite
|
Sign up to set email alerts
|

ENSO's Shrinking Twentieth‐Century Footprint Revealed in a Half‐Millennium Coral Core From the South Pacific Convergence Zone

Abstract: A 492‐year‐long, continuous δ18O time series from a massive Porites coral colony in Ta'u, American Samoa, records contrasting responses to different types of El Niño‐Southern Oscillation (ENSO) through a mixed sea surface temperature and salinity signal. Currently, conventional El Niño (La Niña) events generate cold and salty (warm and fresh) anomalies at Ta'u, while Modoki El Niño (La Niña) events warm (cool) the waters at Ta'u. Over the course of the twentieth century, the Ta'u δ18O record underwent a polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Approximately 20 mol m −2 of CO 2 has been taken up by the upper ocean at each of these study sites
Fig. 3South Pacific coral δ 13 C and skeletal extension rate: coral annual skeletal extensions rates (in blue) and annual average skeletal δ 13 C (black open dots) and δ 13 C data with the average atmospheric 13 C Suess effect removed (solid black dots) in Porites lutea corals from: a Fiji core AB 53 , b Fiji core 1F 52 , c Tonga core TNI2 54 , d Rarotonga core 2R 51,52 , and e American Samoa core Ta’u-1 55,56 . Extension rate and δ 13 C significantly correlate to varying degrees (see R values in Table 1) up until the mid-20th century when coral δ 13 C abruptly shifts ~1.0‰ lower at all of these sites.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 20 mol m −2 of CO 2 has been taken up by the upper ocean at each of these study sites
Fig. 3South Pacific coral δ 13 C and skeletal extension rate: coral annual skeletal extensions rates (in blue) and annual average skeletal δ 13 C (black open dots) and δ 13 C data with the average atmospheric 13 C Suess effect removed (solid black dots) in Porites lutea corals from: a Fiji core AB 53 , b Fiji core 1F 52 , c Tonga core TNI2 54 , d Rarotonga core 2R 51,52 , and e American Samoa core Ta’u-1 55,56 . Extension rate and δ 13 C significantly correlate to varying degrees (see R values in Table 1) up until the mid-20th century when coral δ 13 C abruptly shifts ~1.0‰ lower at all of these sites.
…”
Section: Resultsmentioning
confidence: 99%
“…In November 2011, we cored a large colony of P. lutea on the western side of the island of Ta’u located at S 14° 15′ 33.74″: W 169° 30′ 01.61″ (or S 14 15.566, W 169 30.027) on an exposed outer reef in 7.5 m of water (water depth to top of coral) 55,56 . Prior to slabbing, the longest core, Tau-1, was scanned by X-ray computer automated tomography (CT) to reveal growth bands and to determine the optimal cutting planes (CT collage of coral cores in Tangri et al 56 ). The core was then slabbed on a two-bladed tile saw to produce 5 mm thick slabs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of 19.0 mm year −125 in comparable latitudes and adjusted for an average temperature of 28.4 °C near Ta'u 26 , suggest that the two largest corals found on Ta'u are approximately 368 years and 420 years old, respectively. Another age estimate can be generated using the 490 annual density bands measured by Tangri et al 15 www.nature.com/scientificreports/ between estimates of over 200 years for both corals is noteworthy and illustrates the variability associated with determining ages for long-lived species. One of the most interesting aspects of this study is that multiple massive Porites colonies were documented on three sides of the island, where they are subjected to differing environmental regimes (e.g., wave exposure, wind exposure, ocean current strength, and direction) that may affect growing conditions.…”
Section: Resultsmentioning
confidence: 94%
“…In some studies, the colonies were reported simply as a matter of record for their unusual size [e.g., 13,18]. In other cases, colonies were sampled as part of a larger effort to examine growth rates 17 , temperature records coupled with calcification rates 24 , and climate reconstruction 15 . To our knowledge, none of the reported colonies have exceeded the size of the largest colonies measured from Ta'u.…”
Section: Resultsmentioning
confidence: 99%